Regulatory mechanisms of microRNAs in endocrine disorders and their therapeutic potential - Ledesma-Pacheco, S. Janin; Uriostegui-Pena, Andrea G.; Rodriguez-Jacinto, Estefania; Gomez-Hernandez, Elizabeth; Estrada-Meza, Carolina; Banerjee, Antara; Pathak, Surajit; Ruiz-Manriquez, Luis M.; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) are small endogenous non-coding RNA molecules capable of regulating gene expression at the post-transcriptional level either by translational inhibition or mRNA degradation and have recently been significantly related to the diagnosis and prognosis of the most relevant endocrine disorders. The endocrine system comprises various highly vascularized ductless organs regulating metabolism, growth and development, and sexual function. Endocrine disorders constitute the fifth principal cause of death worldwide. They are considered a significant public health problem due to their long-term effects and negative impact on the patient's quality of life. Over the last few years, miRNAs have been discovered to regulate various biological processes associated with endocrine disorders, which could be advantageous in developing new diagnostic and therapeutic tools. The present review aims to provide an overview of the most recent and significant information regarding the regulatory mechanism of miRNAs during the development of the four most relevant endocrine disorders, including diabetes mellitus, thyroid diseases, osteoporosis, and pituitary tumors, and their potential implications as disease biomarkers.